Production of a fermented drink based on quinoa (Chenopodium quinoa) - Maldonado Jibaja, Roberto; Carrillo Herrera, Paola; Ramírez Cárdenas, Lucía; Carvajal Larenas, Francisco (Enfoque UTE, 2018)
The aim of this study was to develop a beverage obtained from the fermentation of the soluble extract of germinated quinoa under the action of traditional yogurt cultures (S. thermophilus and L. bulgaricus ) and probiotic cultures (Lactobacillus. acidophilus and Bifidobacterium ). Two factors under study were established: the xanthan gum percentage (0.30%, 0.40 % and 0.50% w/w) and sucrose:fructose relation (90:10, 70:30, 50:50) added in the formulation. The quantified variables were: acidity, pH, viscosity and phase separation. The study was conducted under the completely randomized design (CRD), analysis of variance (ANOVA) and Tukey mean separation test with a confidence level of 95 %. The best treatment included 0.50 % xanthan gum and sucrose:fructose relation of 90:10 in its formulation. The product was subjected to sensory tests in which it was determined that the product liked to consumers (score of 3.2 points on a 5-point hedonic scale). Finally, a fermented drink made from quinoa was obtained with 9 g of protein per 200 g of product and with a shelf life estimated in 70 days at 4oC. This product could be an alternative to fermented beverages such as cow's milk yogurt and soy-fermented drink.